1997
DOI: 10.1002/(sici)1097-0134(199702)27:2<195::aid-prot5>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the structure of HIV-1 protease complexed with a hexapeptide inhibitor. Part II: Molecular dynamic studies of the active site region

Abstract: Six models of the catalytic site of HIV-1 protease complexed with a reduced peptide inhibitor, MVT-101, were investigated. These studies focused on the details of protonation of the active site, its total net charge and hydrogen bonding pattern, which was consistent with both the observed coplanar configuration of the acidic groups of the catalytic aspartates (Asp-25 and Asp-125) and the observed binding mode of the inhibitor. Molecular dynamic simulations using AMBER 4.0 indicated that the active site should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The water molecules were added to the binding site of 1hvs because all the water molecules were absent in the experimental structure. Protein protonation states were modeled as in the related HIV-1 protease MD simulation study [56]. All protein residues were modeled in their charged state except for one of the two aspartic acid groups (Asp 25 and Asp 25') in the active site since previous studies [57-59] have shown that at least one of these two aspartic acids is protonated.…”
Section: Methodsmentioning
confidence: 99%
“…The water molecules were added to the binding site of 1hvs because all the water molecules were absent in the experimental structure. Protein protonation states were modeled as in the related HIV-1 protease MD simulation study [56]. All protein residues were modeled in their charged state except for one of the two aspartic acid groups (Asp 25 and Asp 25') in the active site since previous studies [57-59] have shown that at least one of these two aspartic acids is protonated.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the location of protons in the active site may determine the reaction path. This problem has been addressed before ex-perimentally (Hyland et al, 1991a;Ido et al, 1991;Smith et al, 1996;Yamazaki et al, 1994;Wang et al, 1996) and theoretically (Harte and Beveridge, 1993;Chatfield and Brooks, 1995;Geller et al, 1997;Trylska et al, 1999;Piana and Carloni, 2000;Piana et al, 2001). These studies were performed either for the native enzyme or complexed with various inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…These coordinates were also used in modeling studies of inhibitor binding to HIV‐2 PR,29 and to determine the X‐ray structures of several complexes with the recombinant enzyme 30. The structure was used for the molecular mechanics analysis of inhibitor binding to HIV‐1 PR,31, 32 and for a number of molecular dynamics simulation studies 33–35…”
Section: Crystal Structures Of Chemically Synthesized Hiv1‐prmentioning
confidence: 99%